2010
DOI: 10.1111/j.1600-0501.2009.01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Porous titanium granules promote bone healing and growth in rabbit tibia peri‐implant osseous defects

Abstract: The results suggest that PTG and WPTG are both osteoconductive materials that can be used to promote bone formation in osseous defects adjacent to titanium implants without hampering implant osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 32 publications
2
71
0
1
Order By: Relevance
“…Eight prospective clinical studies [22,23,28,29,34,36,38,39], seven case series [24-27,30,33,35], and three randomized clinical trials (RCTs) [31,32,37] were included for the final review. A total of 528 patients (713 implants) were treated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight prospective clinical studies [22,23,28,29,34,36,38,39], seven case series [24-27,30,33,35], and three randomized clinical trials (RCTs) [31,32,37] were included for the final review. A total of 528 patients (713 implants) were treated.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the patients was 61 years (ranged from 20 to 83 years) with the mean observation period of 37 months (ranging from 12 to 236 months). Eleven studies [23-25,27,29,31,32,35-37,39] reported smoking status of the patients, ranging from 14% [39] to 72% [36]. The summarized individual study characteristics are described in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…There were only 60% of the Tigran cases which showed complete re-establishment of the buccal cortical defect, which can be explained by that Tigran granules may need a longer healing period like in CERA-MENT™|BONE VOID FILLER. Tigran is reported to be osteoconductive in experimental osseous defects in conjunction with titanium implants [18]. The retrograde material in this experiment was intermediate restorative material, IRM and it has been reported to be a suitable rootend filling material in periapical surgery procedures [4,19].…”
Section: Discussionmentioning
confidence: 96%
“…14,15 Titanium particles have increasingly used for augmentation procedures, such as sinus lifting, socket preservation, and in the treatment of peri-implantitis. 6,8,[15][16][17] Tissue integration and both two and three-dimensional bone regeneration with Ti particles, however, still need to be explored.…”
mentioning
confidence: 98%